Stress Analysis of Automobile Steering Knuckle Using Finite Element Method - H. Ad Suhadak, F; A. Zakaria, K; B. Ali, M; A. Yusuff, M (International Journal of Engineering and Technology, 2018)
This paper aims in identifying effect of constraint point against critical area of 1300 cc national car steering knuckle using finite element method. The material of this steering knuckle is cast iron ASTM A536. The steering knuckle is modeled using a computer aided design software and the dimensions is assigned according to 3D scanning files. Meanwhile, steering knuckle is simulate using commercial finite element software where the load is assigned based on three conditions of constraints. The three conditions are fixed at hub, fixed hub and brake clamp and fixed at hub, brake clamp and steering arm of steering knuckle. Result shows that the positions of constraint points are significantly effect on stress value of steering knuckle. By acknowledging the presence or absent the effect of constraint on steering knuckle will aid in detecting critical area on this steering knuckle. Thus, approach could be conducted to optimize and enhance the life cycle of a steering knuckle. The data will be further utilized in testing the steering knuckle under variable amplitude strain signal.Â Â